2018
DOI: 10.14412/1996-7012-2018-4-95-100
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and clinical and endoscopic features of mixed NSAIDs-induced gastrointestinal injuries

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) can cause undesirable reactions in all parts of the gastrointestinal tract (GIT). However, the frequency of mixed injuries of various GIT parts due to the use of these drugs has not been investigated.Objective: to estimate the frequency of mixed NSAID-induced injuries of the upper GIT, small and large intestine.Patients and methods. A total of 112 patients (62.5% were women) (mean age, 56.2±14.6 years) with rheumatic diseases who had regularly taken NSAIDs were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
0
0
2
Order By: Relevance
“…They found that half of the patients suffered from gastric and duodenal erosions with ulcers, and hemorrhages in the stomach, duodenum, small bowel, and upper and lower colon. The physicians agreed to link the toxicities with the NSAIDs (Balabantseva et al 2018).…”
Section: Toxicities In Human Studies Gitmentioning
confidence: 99%
“…They found that half of the patients suffered from gastric and duodenal erosions with ulcers, and hemorrhages in the stomach, duodenum, small bowel, and upper and lower colon. The physicians agreed to link the toxicities with the NSAIDs (Balabantseva et al 2018).…”
Section: Toxicities In Human Studies Gitmentioning
confidence: 99%
“…Невыясненные источники ЖКК в указанных работах можно связать либо с диапедезным кровотечением, либо с патологией тонкой кишки [51], эндоскопическая диагностика которой в данных исследованиях не была проведена. По данным РКИ частота развития эрозий и язв тонкой кишки на фоне приема неселективных НПВП составляет 15-25 %, а число ЖКK из тонкой и толстой кишки -0,2-0,3 эпизода на 100 пациентов [52][53][54].…”
Section: структура источников жкк при терапии атсunclassified
“…По данным РКИ, частота развития эрозий и язв тонкой кишки на фоне приема неселективных НПВП составляет 15-25 %, а число ЖКK из тонкой и толстой кишки -0,2-0,3 эпизода на 100 пациентов [51][52][53].…”
Section: структура источников жкк при терапии атпunclassified